Conservation and Production of Woodlands and Royal Forests in the Early Modern Iberian Peninsula - Arroyo, Félix Labrador; Trapaga-Monchet, Koldo (Brill's Series in the History of the Environment, 2026)
Studies on early modern woodlands typically focus on the production, conservation, or management of forests in regard to a specific socio-economic activity (i.e., shipbuilding, mining), or are centred on particular case studies in specific land tenures. This is the first volume to address the production, conservation, and management of woodlands and royal forests on the early modern Iberian Peninsula across different land tenures, forest environments, bioclimatic regions, and jurisdictional arrangements, on a wide spatial and temporal scale. Each chapter offers an innovative argument which is based on solid archival research and an up-to-date bibliography. Contributors are: Ángel Ignacio Aguilar Cuesta, Concepción Camarero Bullón, Ignacio Ezquerra Revilla, Francisco Fernández Izquierdo, José Eloy Hortal Muñoz, Félix Labrador Arroyo, Alfredo José Martínez González, Cristina Joanaz de Melo, Raúl Romero-Calcerrada, and Koldo Trapaga-Monchet.